Cell cycle-dependent phosphorylation regulates RECQL4 pathway choice and ubiquitination in DNA double-strand break repair - Huiming Lu; Raghavendra A. Shamanna; Jessica K. de Freitas; Mustafa Okur; Prabhat Khadka; Tomasz Kulikowicz; Priscella P. Holland; Jane Tian; Deborah L. Croteau; Anthony J. Davis; Vilhelm A. Bohr (Nature Communications, 2017)
DNA double-strand break (DSB) repair is a tightly regulated process that can occur via non-homologous end joining (NHEJ) or homologous recombination (HR). Here, the authors investigate how RECQL4 modulates DSB repair pathway choice by differentially regulating NHEJ and HR in a cell cycle-dependent manner.